ANALYSIS OF CONSUMER DEMAND FOR ORGANIC VEGETABLES IN MATARAM CITY - Mega Silastri Septiana; Amiruddin Amiruddin; Rosmilawati Rosmilawati (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2022)
This study aims to: (1) Analyze the demand for organic vegetables in the city of Mataram, (2) To analyze the factors that influence the demand for organic vegetables in the city of Mataram. the type of data used in this study is qualitative data and quantitative data obtained in the form of not numbers and figures. Data collection methods are through the questionnaire (survey) method using primary data and secondary data. Analysis of the data used in this research is descriptive data analysis used to analyze consumer demand, and statistical data analysis used to analyze the factors that influence the demand for organic vegetables is done by analyzing the cob-douglas function. The results of the analysis show that: (1) the average demand for organic broccoli in Mataram City is 1,300 kg / month, (2) the average demand for organic cucumber vegetables in Mataram City is 2,333 kg / month, (3) the average the average demand for organic eggplant in Mataram City is 1,019 kg / month, (4) the factors that influence the demand for organic broccoli in Mataram are the price of the organic broccoli itself and the price of conventional broccoli, (5) factors that affect the demand for organic cucumber vegetables in Mataram City is the price of organic cucumber itself, the price of conventional cucumber, and consumer tastes, (6) the factors that influence the demand for organic eggplant in Mataram City are the price of organic eggplant itself and the price of conventional eggplant . Keywords: Demand for organic vegetables and the factors that influence demand